Safety Comparison of Monotherapy Aspirin to Dual Antiplatelet Therapy Following Coronary Artery Bypass Surgery. (September 2022) - Nei, Scott D.; Wamsley, Kyle S.; Mara, Kristin C.; Stulak, John M.; Zieminski, Joseph J.
Background: Dual antiplatelet therapy (DAPT) is recommended over single antiplatelet therapy (SAPT) in patients following coronary artery bypass grafting (CABG). The compilation of evidence has focused on the efficacy of DAPT to limit risk of graft occlusion, however the safety, especially in the on-pump CABG population, is less well described. The aim of this study was to assess the safety of DAPT versus SAPT after on-pump CABG. Methods: This was a single-center, retrospective cohort analysis of adult patients following isolated on-pump CABG between January 2012 and December 2019 not on oral anticoagulation at discharge. The primary endpoint was occurrence of a composite bleeding event identified by pre-specified ICD codes. Secondary endpoints consisted of 30-day and 1-year mortalities along with individual bleeding components. Results: Of the 2341 patients included 1250 patients were in the SAPT arm and 1091 patients in the DAPT arm. The study populations differed by age, prior MI, PAD, and CHF status/stage. Bleeding events occurred in a total of 70 patients (3.0%), with 36 patients (2.9%) in the SAPT arm and 34 patients (3.1%) in the DAPT arm ( P  = .74). 30-day (SAPT 0.7% vs DAPT 0.4%) and 1-year (SAPT 3.3% vs DAPT 2.3%) mortality were not significantly different between groups. The most frequent bleed event was in the gastrointestinal tract. Conclusion: In this study, DAPT was not associated with an increase in composite bleeding compared to SAPT. This study could reduce the barrier to prescribing of DAPT given previous efficacy data.